Inter-colony and inter-annual behavioural plasticity in the foraging strategies of a fjord-dwelling penguin—good news in the face of environmental change? - Myrene Otis; Thomas Mattern; Ursula Ellenberg; Robin Long; Pablo Garcia Borboroglu; Philip J. Seddon; Yolanda van Heezik (PeerJ, 2025)
The Fiordland penguin or tawaki (Eudyptes pachyrhynchus) breeds in the complex fjord systems of New Zealand/Aotearoa’s southwest, with penguin colonies distributed from fjord entrances to fjord heads, up to 40 km from the ocean. Until recently, little was known about the marine ecology of fjord-breeding tawaki and how access to the fjord environment may impact the species’ foraging strategies. We conducted a comparative study of foraging behaviour in chick-rearing tawaki from colonies located at the entrance and further inside Piopiotahi/Milford Sound, one of New Zealand’s 14 fjords. Through the attachment of GPS/dive data loggers, dive parameters were examined to determine behavioural differences between the inner fjord colony (Harrison Cove) and the outer fjord colony (Moraine) during 2019 and 2020. Although situated only eight km from each other, the two colonies showed markedly different foraging preferences, with Moraine birds almost exclusively foraging outside the fjord in both years, while Harrison Cove birds primarily foraged within the fjord in 2020 but not in 2019. Tawaki from each colony also displayed contrasting dive behaviour across years, either adopting a strategy of deeper dives with fast velocities, (Harrison Cove in 2019, Moraine in 2020) or shallower dives with slower velocities (Moraine in 2019, Harrison Cove in 2020). Foraging activity and efficiency for both colonies appeared to be greater in 2020 than 2019, although birds foraged differently to achieve this: Harrison Cove birds dived primarily to depths of 0–20 m whereas Moraine birds switched between shallow dives, and deeper dives to 60–120 m of the water column. Notably different environmental conditions in both the ocean and fjord in 2019 versus 2020 may have contributed to the behavioural differences across years. Although replication across multiple fjords is necessary in future, these findings highlight that tawaki possess considerable plasticity in their foraging behaviours which could be advantageous for their future survival in a changing climate.